MLK3 Is Associated With Poor Prognosis in Patients With Glioblastomas and Actin Cytoskeleton Remodeling in Glioblastoma Cells - Zhu, Yan; Sun, Jin-Min; Sun, Zi-Chen; Chen, Feng-Jiao; Wu, Yong-Ping; Hou, Xiao-Yu (Frontiers in Oncology, 2021)
Mixed lineage kinase 3 (MLK3) has been implicated in human melanoma and breast cancers. However, the clinical significance of MLK3 in human gliomas and the underlying cellular and molecular mechanisms remain unclear. We found that MLK3 proteins were highly expressed in high-grade human glioma specimens and especially prevalent in primary and recurrent glioblastoma multiforme (GBM). High MLK3 levels were correlated with poor prognosis in patients with isocitrate dehydrogenase 1 (IDH1)-wild-type (wt) gliomas. Furthermore, genetic ablation of MLK3 significantly suppressed the migration and invasion abilities of GBM cells and disrupted actin cytoskeleton organization. Importantly, MLK3 directly bound to epidermal growth factor receptor kinase substrate 8 (EPS8) and regulated the cellular location of EPS8, which is essential for actin cytoskeleton rearrangement. Overall, these findings provide evidence that MLK3 upregulation predicts progression and poor prognosis in human IDH1-wt gliomas and suggest that MLK3 promotes the migration and invasion of GBM cells by remodeling the actin cytoskeleton via MLK3-EPS8 signaling.